Friday

April 18, 2014

April 18, 2014

Posted by **Shaye** on Thursday, July 12, 2007 at 11:54am.

3x^2=11x+4.

Look up the formula if you don't know it already.

In this case a = 3, b = -11 and c = -4.

You get that by rewriting the equation in the standard form ax^2 + bx + c = 0 , where a, b, and c are constants.

**Related Questions**

Math - Using the quadratic formula solve xsquared=2/3x Using the quadratic ...

Math - Use the quadratic formula to solve each of the following quadratic ...

Algebra - can show me how to do this with out just squaring 3x^(1/2) - x - 6 = 0...

algebra II - Solve using the quadratic formula: x^2 - 3x - 5 = 0

algebra 2 - x^2 - 3x + 5 = 0. solve using quadratic formula. show solution

Algebra - Solve 3x^2+19x-14=0 using the quadratic formula

Algebra - I was given this answers to a problems I solved but I do not ...

Algebra - I was given this answers to a problems I solved but I do not ...

College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...

algebra 2 - How would you solve 3x^2+8x-91=0 and 9r^2+4r+2=0 using the ...